An Analysis Of The English Textbook For The Second YearStudents Of Junior High School Based On The KTSPCurriculum In SMP Muhammadiyah 1 Sragen. - Rahmawati, Putri; , Dr. Anam Sutopo, S.Pd. M.Hum (2016)
The major issues of this study are the material in the English textbook entitled "English in Focus" appropriate or not with KTSP Curriculum and what are the strength and weakness in the English textbook entitled "English in Focus". The objective of this study is to describe the materials in English textbook entitled "English in Focus" based on the KTSP Curriculum or not and to describe the strength and weakness in the English textbook entitled "English in focus". The research is descriptive qualitative research. The writer uses data source English textbook, namely "English in Focus" for the second year students of Junior High School published by Pusat Perbukuan Departemen Pendidikan Nasional and the data of this research are the materials found in the English textbook "English in Focus". The result of the study is first, the writer analysis every skill in the textbook, the skill include Listening, Speaking, Reading and Writing. In the Listening skill has 21 material the 18 materials are appropriate or 85,7% and 3 materials are not appropriate or 14,3%. Speaking skill has 21 materials, the 20 materials are appropriate or 95,3% and 1 material is not appropriate or 4,7%. Reading skill has 6 materials, the 5 materials are appropriate or 83,3% and 1 material is not appropriate or 16,7%. Writing skill has 4 materials, the all of materials are appropriate or 100%. Based on the result of analysis above, the writer can find 90,4% the content of "English in Focus" textbook appropriate with KTSP Curriculum. Second, the writer finds the strength and weakness the English textbook "English in Focus". Based on the result analysis the above, the material in the English textbook appropriate with KTSP curriculum but some material in the content of KTSP Curriculum is not in the textbook. For that the English textbook can help the teaching in process teaching learning. Keywords: Textbook, KTSP Curriculum